COMPETENCY BASED AYURVEDA MEDICAL EDUCATION-W.S.R.TO KRIYA-SHARIR : A REVIEW - Vyas Kartiki (International Journal of Applied Ayurved Research, 2020)
CBME (Competency Based Medical Education) is an approach to produce physicians those are knowledged , skilled and competent to serve the community in spite of producing only graduates. CBME is an objective oriented training model that focuses on the knowledge, skills and attitude empowerment of the learners. The objectives of CBME can be achieved in the Ayurveda field of higher education if it is implicated on the smaller divisions and sub-divisions of the Ayurved Education. Present discussion is focused on applying objectives of CBME in a single subject (programme specific) Kriya –Sharir of 1st B.A.M.S. programme. Competency based education can be applied to Ayurveda education specifically for the Ayurveda concepts in such a way that all cognitive, psychomotor and affective domains can be achieved by learners in an effective way through different methodologies.